Knowledge and innovation for competitiveness in Brazil - Rodriguez, Alberto, 1965- (WBI development studies., 2008)
The research presented in this volume explains how well-educated workers can interact with physical capital inputs to innovate and add value to processes, products and services, ultimately creating a multiplier-effect on macroeconomic growth. It fills a significant gap in the existing literature by providing a detailed map of the relationship between microeconomic inputs such as health and education services and macroeconomic outputs such as growth. Grounded in economic theory and backed by economic analysis, Knowledge and Innovation for Competitiveness makes a compelling argument that human c.